Analysis of the Implementation of Kaizen Culture on Work Effectiveness in the Food & Beverage Service at Rizzan Sea-Park Tancha-Bay Hotel - Zainal Lamakarate; Mirjam Pratidina Tenda; Machiko Nugraha Indriyanto; Benny Irwan Towoliu (Jurnal Internasional Riset Bisnis Pariwisata, 2025)
This study aims to analyze the implementation of Kaizen culture and its influence on work effectiveness within the Food & Beverage Service department at Rizzan Sea-Park Tancha-Bay Hotel, Okinawa, Japan. The Kaizen philosophy rooted in continuous improvement and employee participation has been widely applied in manufacturing sectors, yet its adaptation in hospitality remains underexplored. Employing a qualitative descriptive approach, data were collected through in-depth interviews, participatory observation, and analysis of operational documents involving managers, assistant managers, and service staff directly engaged in daily operations. The findings reveal that the integration of PDCA, 5S, and 3M principles fosters a structured, efficient, and disciplined work environment. The PDCA cycle promotes continuous evaluation and learning, the 5S framework enhances hygiene and orderliness, and the 3M elimination process optimizes workload balance and resource efficiency. Together, these practices contribute to improved service speed, reduced operational waste, and higher guest satisfaction. Key success factors include top management commitment, participatory leadership, and continuous training, while challenges involve sustaining employee awareness and cross-cultural adaptation among diverse staff. This research extends Kaizen theory by demonstrating its transferability from manufacturing to high-contact service industries, highlighting its dual role as a technical and cultural system of improvement. Practically, the study provides insights for hospitality managers seeking to institutionalize Kaizen as a sustainable approach to operational excellence and human-centered performance development.